2015
DOI: 10.1111/jgh.12840
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography compared to serum markers to predict liver fibrosis in a cohort of Chinese patients with chronic hepatitis B

Abstract: Background and Aim: Liver stiffness measurement (LSM) using transient elastography (FibroScan) is a useful tool to assess fibrosis in various chronic liver diseases. However, studies were mainly performed in Western countries and largely focused on chronic hepatitis C (CHC). We therefore carried out a multicenter study to validate the accuracy of LSM in the assessment of liver fibrosis in a large cohort of Chinese patients with chronic hepatitis B (CHB). Methods: We compared LSM results to histological staging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 30 publications
6
75
1
Order By: Relevance
“…In our cohort of patients with CHB, we demonstrated the good performance of LSM in staging significant fibrosis (S3‐S6) and advanced fibrosis (S4‐S6). Our result is in agreement with previous studies . The optimal cut‐offs in our study of patients with CHB are also comparable to those identified in other studies …”
Section: Discussionsupporting
confidence: 93%
“…In our cohort of patients with CHB, we demonstrated the good performance of LSM in staging significant fibrosis (S3‐S6) and advanced fibrosis (S4‐S6). Our result is in agreement with previous studies . The optimal cut‐offs in our study of patients with CHB are also comparable to those identified in other studies …”
Section: Discussionsupporting
confidence: 93%
“…A study by Jia et al . showed that liver elastometry got high AUROCs of 0.82, 0.88, and 0.90 for the diagnoses of advanced fibrosis, severe fibrosis, and cirrhosis, respectively 13 . Recently, the study by Shi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with moderate‐to‐severe inflammation (A3 or higher) and/or fibrosis (F2 or higher) can be considered for antiviral therapy . Noninvasive methods may be used in lieu of liver biopsies to assess for severity of fibrosis and/or inflammation . Liver stiffness measurements (elastrography) are more accurate than serum fibrosis panels (e.g.…”
Section: Follow‐up Of Patients Not Currently On Antiviral Treatmentmentioning
confidence: 99%
“…aspartate aminotransferase [AST] to platelet ratio index or FIB‐4) in predicting significant or advanced fibrosis . Noninvasive methods overestimate fibrosis if high levels of necroinflammation, as reflected by elevated ALT, are present …”
Section: Follow‐up Of Patients Not Currently On Antiviral Treatmentmentioning
confidence: 99%